2003
DOI: 10.1159/000068858
|View full text |Cite
|
Sign up to set email alerts
|

A True Splenic Cyst Producing Carbohydrate Antigen 19-9 and Cancer Antigens 50 and 125, but Not Interleukin 10

Abstract: A giant cystic lesion of the left upper abdomen associated with a smaller ovarian cyst in a young female patient is reported. Laboratory data revealed elevated serum levels of carbohydrate antigen 19-9 (CA 19-9), carcino-embryonic antigen (CEA), cancer antigens 50 and 125, and tissue polypeptide antigen. In contrast, the serum levels of interleukin 10, a cytokine involved in modulating immune responses and produced by many cancer histotypes, were normal. Since ovarian cancer or cystic adenocarcinoma of the tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Abnormal CEA levels may mislead the diagnosis, as several benign disorders involving increased CEA were described in the literature, including rheumatoid arthritis (20), appendiceal mucocele (57), true splenic cyst (58) and a case report of a patient with bronchial asthma and mucoid impaction (59). Sasaki et al have suggested that CEA assessment could serve as a prognostic factor in predicting the future regression of simple ovarian cysts (60), and Pinto et al have shown that combination of CEA and Ca125 measurements could be helpful in the distinction of functional from epithelial ovarian cysts (61).…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Abnormal CEA levels may mislead the diagnosis, as several benign disorders involving increased CEA were described in the literature, including rheumatoid arthritis (20), appendiceal mucocele (57), true splenic cyst (58) and a case report of a patient with bronchial asthma and mucoid impaction (59). Sasaki et al have suggested that CEA assessment could serve as a prognostic factor in predicting the future regression of simple ovarian cysts (60), and Pinto et al have shown that combination of CEA and Ca125 measurements could be helpful in the distinction of functional from epithelial ovarian cysts (61).…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…In addition, true cysts occur mainly in children and young adults [19], with approximately two-thirds of patients being female [20]. In the literature, approximately 190 reports pertaining to true splenic cysts have been documented, and of these, only a few describe spontaneous cyst rupture [20][21][22][23][24][25][26][27]. The origin of epithelial [true] cysts of the spleen is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors attribute their development to the embryonic inclusion of epithelial tissue, whereas others refer to the inclusion of the mesothelial lining with subsequent squamous metaplasia [28,29]. In addition, there are recent reports in the literature describing high serum levels of tumor markers (CA 19-9, CEA, cancer antigens 50 and 125) [23][24][25]. These reports indicate that the production of CEA, CA 19-9, and, to a lesser extent, cancer antigens 50 and 125 is dependent on the epithelium lining of the true cysts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation